Current approach to genetic testing and genetic evaluation referrals for adults with congenital heart disease - Oehlman, Laura B.; Opotowsky, Alexander R.; Weaver, Kathryn N.; Brown, Nicole M.; Barnett, Cara L.; Miller, Erin M.; He, Hua; Shikany, Amy R. (Frontiers in Genetics, 2024)
Background Congenital heart disease (CHD) is the most common congenital anomaly. Up to 33% have an identifiable genetic etiology. Improved medical and surgical management of CHD has translated into longer life expectancy and a rapidly growing population of adults living with CHD. The adult CHD (ACHD) population did not have access during childhood to the genetic technologies available today and therefore have not had a robust genetic evaluation that is currently recommended for infants with CHD. Given this potential benefit; the aims of this study were to determine how ACHD cardiologists offer genetics services to patients and identify the indications that influence decision-making for genetics care. Methods We performed a descriptive cross-sectional study of ACHD cardiologists. A study-developed questionnaire was distributed via emailed REDCap link. The recruitment email was sent to 104 potential respondents. The survey was open from 06/2022 to 01/2023. Results Thirty-five cardiologists participated in the study (response rate of 34%). Most cardiologists identified as white (77%) and male (66%). Cardiologists were more likely to refer patients to genetics (91%) than to order testing themselves (57%). Of the testing ordered, chromosomal testing (55%) was ordered more than gene sequencing (14%). Most cardiologists would refer a patient with a conotruncal lesion (interrupted aortic arch) over other indications for a genetics evaluation. There were more reported barriers to ordering genetic testing (66%) compared to referring to genetics for a genetics evaluation (23%). Cardiologists were more confident recognizing features suggestive of a genetic syndrome than ordering the correct test (p = 0.001). Regarding associations between clinical factors and current practices, more years in practice trended towards less referrals and testing. Evaluating a greater number of patients (p = 0.11) and greater confidence recognizing syndromic features (p = 0.12) and ordering the correct test (p = 0.09) were all associated with ordering more testing. Conclusion Testing for microdeletion syndromes is being offered and completed in the ACHD population, however testing for single-gene disorders associated with CHD is being under-utilized. Developing guidelines for genetic testing in adults with CHD could increase access to genetic services, impact medical management, reduce uncertainty regarding prognosis, and inform recurrence risk estimates.